Hydrological modeling of soil-water availability in the Caatinga biome - Pinheiro, Everton Alves Rodrigues (2016)
Northeastern Brazil is hydrologically characterized by recurrent droughts leading to a highly vulnerable natural water resource system. The region contains the Caatinga biome, a sparsely studied ecosystem, covering an area of approximately 800,000 km2. Reduced wateravailability is projected to take place in large regions of the globe, including Northeastern Brazil. Given the strong interactions between climate and vegetation, research has addressed climate change effects on natural and agricultural ecosystems. In this context, soil hydraulic properties are essential to assess soil water flow, and thus the ability of soil to supply water to plants at potential rates under different ranges of pressure head. Based on that, the aims of this thesis are: to increase insight in water balance components for the Caatinga biome, under current and future climate scenarios; and to assess the ability of soils in supplying water to plants by the further development of an existing matric flux potential approach, followed by its application to a group of soils from two Brazilian climatic zones (semi-arid and subhumid). Both for current and future climate scenarios, hydrological simulations were performed with SWAP model parameterized for a preserved Caatinga basin of 12 km2. The validation of the simulations was performed using a dataset of daily soil-water content measurements taken at 0.2 m depth in the period from 2004 to 2012. The soil water supplying capacity was evaluated through a multilayer matric flux potential approach, coupling the soil hydraulic properties, root length density and plant transpiration. Regarding the current climate conditions, the Caatinga biome returns 75% of the annual precipitation to the atmosphere, whereas the partitioning of total evapotranspiration into its components (transpiration, evaporation and interception) on annual basis accounts for 41%, 40% and 19%, respectively. Evapotranspiration and air temperature are most sensitive to soil moisture during the periods June-September and December-January. Concerning the future climate, transpiration was enhanced by 36%, soil evaporation and interception losses reduced by 16% and 34%, respectively. The amount of precipitation returned to the atmosphere was on average 98%. For both climate scenarios, the soil-plant-atmosphere fluxes seem to be controlled by the surface soil layer (0-0.2 m) which provides, on average, 80% of the total transpiration, suggesting that the Caatinga biome may become completely soil-water pulse dominated under scenarios of reduced water availability. The matric flux potential analysis revealed that soils from the semiarid zone were able to deliver water to plants at potential rates under a wider range of bulk soil pressure head (-36 to -148 m), whereas the soils from the wetter zone showed more hydraulic restriction with limiting soil water potential above -1.5 m. For the analyzed soils, only a negligible increase in available water results from decreasing the root water potential below -150 m, therefore, in order to adapt to water-limited conditions, plant species may invest in other adaptive strategies, rather than spending energy in structures that allow a reduction of the lower suction limit in their tissues.